Comparative evaluation of subgingivally delivered xanthan-based chlorhexidine gel and herbal extract gel in the treatment of chronic periodontitis - Phogat, Megha (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Local drug delivery agents can effectively deliver the antimicrobial drugs in bactericidal concentration, and have shown improved clinical outcomes when used as an adjunct to mechanical therapy. The aim of this study was to evaluate the efficacy of a xanthan-based chlorhexidine gel versus herbal extracts’ gel as an adjunct to periodontal therapy in the treatment of chronic periodontitis. MATERIALS AND METHODS: A total of 150 sites, age group of 30-50 years, periodontal pockets measuring 5-8 mm and diagnosed with chronic periodontitis were selected for the study. The selected sites were randomized in five groups: Scaling and root planing (SRP) alone (Group A), SRP + Chlosite gel (Group B), SRP + Herbal gel (Group C), Chlosite gel alone (Group D) and Herbal gel alone (Group E). Clinical parameters such as Plaque Index, Gingival Index, probing pocket depth and clinical attachment level were recorded at baseline and 1- and 3-month intervals. RESULTS: After 3 months, there were statistically significant reductions in all the clinical parameters for Groups B and C compared with Group A. There was no significant reduction in all clinical parameters between Group D and E where no mechanical therapy was performed. CONCLUSION: The results indicate that the local application of herbal gel can be comparably used as chlorhexidine gel in the treatment of chronic periodontitis as an adjunct to mechanical periodontal therapy.